IMPROVED FUZZY SET THEORY FOR SOLVING MULTI CRITERIA DECISION MAKING PROBLEMS IN PRODUCT DESIGN - Mr.Prakash Bapurao Fulari, Dr. Dilip Bapurao Ghule, Dr. VineetaBasotia (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Multi Criteria Decision Making (MCDM)aims to provide decision forproblems under complex decision making environmentwhich considered as critical task in various applications such as product design, service provider selection and quality selection.In literature, some efficient techniques are available to find the optimal selection with respect to the criteria. These methods are fails to attain high selection accuracy due to increased cost, unwanted data entry, low quality of product and wastage of time. Hence, in this proposed methodology, improved Hierarchical-Fuzzy (H-Fuzzy)set theory is designed to solve the MCDM problems in product design applications. The proposed H-Fuzzy theory is used to optimal selection of product tool selection by using normalized average weight gain operation. The proposed H-Fuzzy set theory is working based on two main steps such as priority weighting and normalized weighting. The priority weighting is achieved in H-Fuzzy theory and the overall priority weights alternatives determined. Based on these overall priority weights, the alternatives are ranked. The ranking process is considered as final step of proposed methodology which selected the optimal product tool. The proposed H-Fuzzy set theory is implemented in a MATLAB platform and its performances were evaluated. The statistical measurements are considered to analysis the performance of the proposed methodology such as accuracy, sensitivity, specificity, and kappaand error measurement. The outcome shows that the proposed model is better than the previous ones.